The Influence of Organizational Culture on Employee Performance at CV. Sumber Wangi, Makassar City - Andy Chairuddin; Andi Aris Mattunruang; Suarlin Suarlin (SAINTIS Publishing, 2025)
This study explores the relationship between organizational culture and employee performance at CV. Sumber Wangi in Makassar City. Utilizing a saturated sampling technique, the research involved all 30 members of the population as participants. Data collection methods included questionnaires, documentation, and direct interviews with relevant stakeholders. Hypothesis testing was conducted using the t-test (partial) and the coefficient of determination with the assistance of SPSS 25. Findings revealed that organizational culture positively and significantly influences employee performance both partially and simultaneously. This was substantiated by the t-test results, where a significance value of 0.047 (0.05) confirmed the effect of organizational culture on performance. Additionally, the coefficient of determination test showed that organizational culture accounts for 10.2% of the variance in employee performance, as indicated by an Adjusted R value of 0.102. These results underscore the importance of organizational culture in shaping employee performance, while also suggesting the presence of other factors that contribute to the remaining 89.8% of the variance.